THE USE OF PICTURE MEDIA SERIES AS LEARNING MEDIA FOR DYSLEXIA SYMPTOMS STUDENTS - Mashuri, Mashuri; Khaira, Wanty; Mulia, Mulia; Rieska, Rieska (Prodi PGMI FTK UIN Ar-Raniry Banda Aceh, 2024)
This research aims to determine the effectiveness of using serial image media as a learning medium to help dyslexia symptoms students' reading abilities. The sample of this study consisted of 2 dyslexia symptoms students in class II-1 MIN 11 Banda Aceh. This research method has used pre-experimental with a one group pre-test-post-test design. Data were collected through treatment procedures by using serial image media. Then, the techniques of analysis are using normality tests and hypothesis testing. The research results show that the use of serial image media can improve effectively the reading ability of dyslexia Symptoms students and learning activities besides reading motivation of dyslexia students have increased either. So it can be concluded from the research results that Ha is accepted and Ho is rejected, in other words there is a difference in the level of reading ability before and after the use of serial image media in dyslexic students at MIN 11 Banda Aceh.Key Word: Pictures Series